Relationship between Formula Milk and the Incidence Obesity in Children Under Five: Meta-Analysis - Yopiana, Elma; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Obesity is a nutritional disorder that most often occurs in children. Obesity is associated with worse health outcomes in children, including asthma and sleep apnea. This study aimed to examine the relationship between formula feeding and obesity in children under five.Subjects and Method: This was a meta-analysis study conducted by systematically reviewing articles from PubMed, Science Direct, Springer Link, and Google Scholar. The articles used in this research are articles that have been published from 2008-2016. The search for articles was carried out by considering the eligibility criteria using the PICO model, P: toddlers, I: formula feeding, C: breastfeeding, O: obesity. The key words for finding articles were as follows: